SOCIOLOGICAL APPROACHES IN ISLAMIC STUDIES (Concepts and Relevance in Society) - Muh Syauqi Malik; Arina Zulva Maulida; Maslahah Maslahah (Tatar Pasundan: Jurnal Diklat Keagamaan, 2022)
Diversity does not always get a positive response from the community because diversity often conflicts with developing cultures. This article aims to discover the sociological approach in Islamic studies. The library research method is used with a variety of relevant sources. The study results indicate that the sociological characteristics of Islamic studies emphasize muamalah worship rather than ubudiyah. Theories in the sociological approach include functional theory, interactional theory, and conflict theory. Sociological methods in Islamic studies include descriptive, comparative, and experimental methods. Islamic sociology pays attention to problems developed in society, such as the prohibition of usury, reducing the divorce rate, and socio-political comparability. This article also contains a case analysis of society's sociological approach.Keywords: Sociological Approach; Sociology; Islamic Studies